O homem do sertão e o narrador: da cultura popular e do foco narrativo em Sagarana (Uma Leitura dos Contos O Burrinho Pedrês , A Volta do Marido Pródigo , São Marcos e Corpo Fechado ) - Lucena, Gilberto de Sousa (2013)
This paper aims to study aspects of popular culture and the narrative focus in the tales O Burrinho Pedrês , A Volta do Marido Pródigo , São Marcos e Corpo Fechado inserted in Sagarana, a book of the writer from Minas Gerais João Guimarães Rosa (1908-1967), which was published in 1946. In a theoretical approach of the short story, understood as a fictional genre multifaceted we will contemplate the range of social representation as a literary element and the role of the narrator to legitimize values of popular culture related to codes of honor that exist within the rural community literally represented in each of the highlighted stories. Regarding this aspect, we will try to show the position of commitment of the voice that narrates with certain values of the universe of popular culture focused on the analyzed corpus.